On- vs off-hours primary percutaneous coronary intervention: a single-centre experience. (14th October 2021) - Mane, F G; Flores, R; Silva, R; Conde, I; Rodrigues, C; Medeiros, P; Oliveira, C; Campos, I; Ferreira, A S; Costa, J; Quina, C; Braga, C; et al.
Abstract: Introduction: In ST-segment elevation myocardial infarction (STEMI) patients, emergency medical system delays importantly affect outcomes. The effect of admission time in STEMI patients is dubious when percutaneous coronary intervention (PCI) is the preferred reperfusion strategy. Aims: The authors aimed to retrospectively describe the association between admission time and STEMI patient's care standards and outcomes. Methods: Characteristics and outcomes of 1222 consecutive STEMI patients treated in a PCI-centre were collected. On-hours were defined as admission on non-national-holidays from Monday to Friday from 8 AM to 6 PM. Time delays, in-hospital and one-year all-cause mortality were assessed. Results: A total of 439 patients (36%) were admitted on-hours and 783 patients (64%) were admitted off-hours. Baseline characteristics were well-balanced between groups, including the percentage of patients admitted in cardiogenic shock (on-hours: 4.6% vs off-hours 4%; p=0.62). Median emergency system dependent time to reperfusion (i.e. first-medical contact to reperfusion) did not differ between the two groups (on-hours: 120 min vs. off-hours 123 min, p=0.54). The authors observed no association between admission time and in-hospital mortality (on-hours: 5% vs. off-hours 4.9%, p=0.90) or 1-year mortality (on-hours: 10% vs. off-hours 10%, p=0.97). In patients admitted directly in the PCI-centre, median time from first-medical contact to reperfusion (on-hours: 87 min vs off-hours: 88 min, p=0.54), in-hospital mortality (on-hours: 4% vs off-hours: 7%, p=0.30) and 1 year mortality (on-hours: 9% vs off-hours: 13%, p=0.27) did not differ between the two groups. Survival analysis showed no survival benefit of on-hours PCI over off-hours PCI (HR 1.01; 95% CI [0.77–1.46], p=0.95). Conclusion: In a contemporary well-organized emergency network, STEMI patients admission time in the PCI-centre was not associated with reperfusion delays or increased mortality. FUNDunding Acknowledgement: Type of funding sources: None.